Uji Aktivitas Antibakteri Ekstrak Etanol Sereh Wangi (Cymbopogon nardus L. Rendle) Terhadap Pertumbuhan Bakteri Staphylococcus aureus ATCC 25923 Menggunakan Metode Sumuran - Leswara, Dianita Febrina; Enggrainia, Bella; Pratama, Nofran Putra (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) UNIVERSITAS JENDERAL ACHMAD YANI YOGYAKARTA, 2024)
Background: Bacteria are one of the organisms that cause infectious diseases. One of the bacteria that can cause infection is Staphylococcus aureus. Treatment of bacterial infections is by using antibiotics, but using the antibiotics for a long term can cause resistance. It is necessary looking for alternative compounds that can inhibit the growth of Staphylococcus aureus. Cymbopogon nardus L. Rendle is a plant that has antibacterial compound, that compounds are flavonoids and tannins.Objective: To determine the antibacterial activity of Cymbopogon nardus ethanol extract against the growth of Staphylococcus aureus ATCC 25923 using the well method.Method: Cymbopogon nardus is extracted using the maceration method with 70% ethanol solvent. A phytochemical screening test was carried out and continued with an antibacterial activity test using the well method with concentrations of 5%, 10%, 15% and 20%.Results: Phytochemical screening show that Cymbopogon nardus ethanol extract contains saponins, flavonoids, steroids and tannins. The results of the antibacterial test showed that the average inhibitory zone value of Cymbopogon nardus ethanol extract at concentrations of 10%, 15% and 20% was 23.00; 23.77; 24.96 mm, whereas at concentration of 5% it did not show an inhibition zone for the Staphylococcus aureus ATCC 259323 bacteria.Conclusion: Cymbopogon nardus ethanol extract has antibacterial activity against the growth of Staphylococcus aureus ATCC 259323 with a minimum inhibitory concentration (MIC) which is able to inhibit the growth of Staphylococcus aureus ATCC 259323 at concentration of 10%, for concentrations of 10%, 15% and 20% it has an inhibitory power of very strong category.